Feeding Rate and Success Rate of Foraging Waders in Tropical Intertidal Areas - Norazlimi, Nor Atiqah; Ramli, Rosli; Hasmi, Nur Atirah (UTHM, 2020)
A serious deduction in waders population worldwide has led to several study on ecology of waders in their stop-over migratory routes. Extensive study on wader’s habitat used especially on their feeding ground is needed to establish a framework that channels to the conservation of waders species. Therefore, this study was aimed to determine the feeding and success rates of foraging in selected species of waders at Jeram and Remis Beaches of Selangor, Malaysia. Direct observation techniques were used in this study. Kruskal-Wallis Analysis test shows that there was significant difference in feeding rates (H= 139.58, p < 0.001) and success rates between the species (H = 11.18, p = 0.011). Pairwise comparisons analysis proved that the differences of feeding rates occurred between Little heron and Lesser adjutant (z = 107.39, p < 0.0001); Little heron and Whimbrel (z = -159.31, p < 0.001); and Lesser adjutant and Common Redshank (z = 80.3, p < 0.001). Meanwhile, Mann-Whitney test shows that the differences lie between Little heron and Common redshank (W = 5743, p = 0.0114) and also between Lesser adjutant and Common redshank (W = 9353, p = 0.012). Spearman correlation shows that a significant correlation was found between both feeding and success rates (R = -0.293, p < 0.001). This study concluded that the feeding rates and success rates were differed between different species of waders utilizing similar feeding ground due to the differences in foraging techniques used while foraging.